(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Since cancer is a complex illness, a multimodal strategy with a multidisciplinary team is necessary. Currently, chemotherapy, surgery, and/or radiation therapy are used in combination to treat cancer. Chemotherapy is currently recognized as the most effective cancer treatment, despite the fact that it is known to induce severe side effects in patients due to its non-discriminatory adverse effect on both normal and malignant cells. Understanding how drugs are distributed throughout organs and creating a site-specific drug delivery strategy that targets cancer cells are the primary problems in cancer and other complex chemotherapeutic diseases. Thus, it is essential to create innovative methods for the traceable and targeted delivery of anti-cancer drugs. This review article's objective is to provide an overview of current tumor therapy methods and discuss their potential benefits in a multimodal strategy. There is growing optimism that significant improvements in illness diagnosis and treatment may result from the use of nanotechnology in medicine. Additionally, this review article offers an overview of multifunctional nanostructures used in medication delivery and cancer therapy.